Interventions to promote oral nutritional behaviours in people living with neurodegenerative disorders of the motor system: A systematic review. Issue 8 (August 2020) - Essat, Munira; Archer, Rachel; Williams, Isobel; Zarotti, Nicolò; Coates, Elizabeth; Clowes, Mark; Beever, Daniel; Hackney, Gemma; White, Sean; Stavroulakis, Theocharis; White, David; Norman, Paul; et al.
Summary: Background & aims: Weight loss is common in people with neurodegenerative diseases of the motor system (NDMS), such as Parkinson's disease and Amyotrophic Lateral Sclerosis, and is associated with reduced quality of life, functional ability and survival. This systematic review aims to identify interventions and intervention components (i.e. behaviour change techniques [BCTs] and modes of delivery [MoDs]) that are associated with increased effectiveness in promoting oral nutritional behaviours that help people with NDMS to achieve a high calorie diet. Methods: Eight electronic databases including MEDLINE and CINAHL were searched from inception to May 2018. All interventions from included studies were coded for relevant BCTs and MoDs. Methodological quality of studies was assessed using the Cochrane risk of bias tool. Results: Fourteen studies were included. Of these, eight studies reported interventions to assist with swallowing difficulties and six studies reported interventions targeting dietary content. Beneficial effects in managing swallowing difficulties were observed with video assisted swallowing therapy, lung volume recruitment and swallowing management clinics with outpatient support. In contrast, studies reporting effectiveness of chin down posture, use of thickened liquids and respiratory muscle training were inconclusive. Positive effects in interventions targeting dietary content included the use of food pyramid tools, individualised nutritional advice with nutritional interventions, electronic health applications, face-to-face dietary counselling and high fat, high carbohydrate and milk whey protein supplements. Individualised nutritional advice with weekly phone contact did not appear to be effective. Most frequently coded BCTs were 'instructions on how to perform the behaviour', 'self-monitoring' and 'behavioural practice/rehearsal'. Most commonly identified MoDs were 'human, face-to-face' and 'somatic therapy'. However, the robustness of these findings are low due to the small number of studies, small sample sizes and large between-study variability. Conclusions: Despite the limited evidence, these findings may help inform the development of more effective interventions to promote oral nutritional behaviours in people with NDMS. However, further research is needed to demonstrate which interventions, or intervention components, yield most benefit.